Predictors of Extended Length of Stay following Treatment of Unruptured Adult Cerebral Aneurysms: A Study of the National Inpatient Sample. (16th November 2020) - Koo, Andrew B; Elsamadicy, Aladine A; Lin, I-Hsin; David, Wyatt; Freedman, Isaac G; Sujijantarat, Nanthiya; Cord, Branden; Hebert, Ryan M; Bahrassa, Farhad; Malhotra, Ajayy; Matouk, Charles C
Abstract: INTRODUCTION: For the treatment of unruptured cerebral aneurysms, the determinants of extended length of stay are relatively unknown. METHODS: The National Inpatient Sample years 2010–2014 was queried. Adults with unruptured aneurysm undergoing either clipping or coiling were selected using the ICD-9-CM coding system. Extended LOS was defined as greater than 75 th percentile for the entire cohort (>5 days). Weighted patient demographics, comorbidities, complications, LOS, disposition and total cost were recorded. Multivariate logistic regression was used to determine the odds ratio for risk-adjusted extended LOS. The primary outcome was the degree patient comorbidities or postoperative complications correlated with extended LOS. RESULTS: A total of 46, 880 patients were identified for which 9, 774 (20.8%) patients had extended LOS (Normal LOS: 37, 106; Extended LOS: 9, 774). Patients in the extended LOS cohort presented with a greater number of comorbidities compared to the normal LOS cohort. A greater proportion of the normal LOS cohort was coiled (Normal LOS: 63.0% vs. Extended LOS: 33.5%, P < . 001), while more patients in the extended LOS cohort were clipped (Normal LOS: 37.0% vs. Extended LOS: 66.5%, P < . 001). The overall complication rates were greater in the extended LOS cohort (Normal LOS: 7.3% vs. Extended LOS: 43.8%, P < . 001). On average, the extended LOS cohort incurred a total cost nearly twice as large (Normal LOS: $26, 050 ± 13, 430 vs. Extended LOS: $52, 195 ± 37, 252, P < . 001) and had more patients encounter non-routine discharges (Normal LOS: 8.5% vs. Extended LOS: 52.5%, P < . 001) compared to the normal LOS cohort. On weighted multivariate logistic regression, multiple patient-specific factors were associated with extended LOS. These included demographics, preadmission comorbidities, choice of procedure, and inpatient complications. The odds ratio for extended LOS was 5.14 (95% CI, 4.30 - 6.14) for patients with 1 complication and 19.58 (95% CI, 15.75 - 24.34) for patients with > 1 complication. CONCLUSION: Our study demonstrates that extended length of stay after treatment of unruptured aneurysms is influenced by a number of modifiable patient-specific factors, including both pre- and peri-operative variables.